PENINGKATAN PENGETAHUAN GIZI KELUARGA MELALUI PENYULUHAN DAN INOVASI PMT NUGGET IKAN LELE UNTUK BALITA DI DESA MENANTI - Anggi Anggraini; Rizka Maulana Zulfa; Syafitri; Khafifah Hazriati Repalia; Afiza Indah Nurhidayah; Hanim Fadhilah; Ayu Prameswari (Departement of Environmental Health, Faculty of Public Health, Sriwijaya University, 2025)
The problem of toddler nutrition in Menanti Village is still high due to the lack of family knowledge about balanced nutrition and low consumption of animal protein. This community service activity aims to improve the understanding of mothers of toddlers through counseling and innovation in providing additional food made from catfish nuggets, which are easily available and have high nutritional value. The methods used include pre-test, interactive counseling, leaflet distribution, and post-test to measure changes in knowledge. The results showed an increase in the average value of mothers' knowledge from 73.60 to 96.80 after the intervention, with a statistically significant difference. This activity proves that nutrition education combined with local food innovation can improve family nutrition knowledge and practices, thus potentially improving the nutritional status of toddlers in similar areas.